Where do we go from here? Reappraising the data on anticoagulation in pulmonary arterial hypertension - Cirulis, Meghan M. (J Thorac Dis, 2016)
The use of anticoagulation as part of the treatment regimen in pulmonary arterial hypertension (PAH) remains a topic of debate. A recently published analysis of anticoagulation use in the Registry to Evaluate Early and Long-Term PAH Disease Management (REVEAL) study offers conflicting conclusions regarding the benefit of this therapeutic strategy. There remains no robust randomized trial in PAH weighing the risks versus benefits of including anticoagulation in treatment regimens, leaving clinicians to surmise value in individual patients. Reexamination of available data may help to provide guidance on this controversial topic in the absence of future dedicated investigations.